Primary pleural epithelioid hemangioendothelioma mimicking as a posterior mediastinal tumor. Issue 2 (18th May 2015) - Wethasinghe, James; Sood, Jaideep; Walmsley, Russell; Milne, David; Jafer, Ali; Gordon‐Glassford, Noel
Abstract A 41‐year‐old man with no previous asbestos exposure presented with 6 months of dull right lower chest pain and weight loss. The initial computed tomography (CT) scan was reported as showing a soft tissue thickening in the posterior mediastinum with non‐specific nodules in the horizontal and oblique fissures. An endoscopic ultrasound‐guided fine needle aspiration from the 12 × 25 mm heterogeneous posterior mediastinal mass was suspicious for a ganglioneuroma. The procedure was complicated by a large hemothorax requiring drainage. A subsequent positron emission tomographic CT revealed a moderately fluorodeoxyglucose avid area of pleural thickening extending from the sixth to ninth thoracic vertebral body in the paraspinal region along with nodules along the right horizontal and oblique fissures. A thoracoscopic biopsy of the pleural lesion confirmed a pleural epithelioid hemangioendothelioma. There was a 5‐mm reduction in tumor thickness and improvement in his pain following 54 Gy of radiotherapy.